EVALUASI KELAYAKAN TAHANAN ISOLASI TRANSFORMATOR 30 MVA MENGGUNAKAN METODE INDEKS POLARISASI DAN TANGEN DELTA: Transformer, Polarization Index, Tan Delta - Gunawan, Muhammad Erwin; Haddin, Muhammad (LP2M Universitas Nurdin Hamzah, 2025)
Use of a 30 MVA Auxiliary Transformer (UAT) Unit for a long period of time can experience insulation suitability problems, resulting in overvoltage and a decrease in insulation resistance. Humidity and high temperatures are factors that can cause mechanical damage which results in stopping the flow of electricity to the load. As a solution, the research carried out a feasibility test for the insulation resistance of a 30 MVA auxiliary transformer unit with a model determined as a transformer whose insulation feasibility was tested. The test uses the polarization index and tangent delta methods referring to the IEEE 43-2000 and ANSI C57.12.90 standards. The polarization index values obtained were 1.91 for HV-LV1+LV2+GND, 2.49 for LV1-HV+LV2+GND, and 1.87 for LV2-HV+LV1+GND. The tangent delta value in the 30 MVA Auxiliary Transformer Unit measurement is 0.323% for Primer ,0,949% for Secunder, and 0,834 for Tertier. These values indicate that the UAT isolation condition is still in good condition and suitable for operation.